Gelation of covalently edge-modified laponites in aqueous media. 1. rheology and nuclear magnetic resonance - Patil, Suhas P.; Mathew, Renny; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Mahesh, T. S.; Kumaraswamy, Guruswamy (Journal of Physical Chemistry B, 2008)
We describe the covalent modification of the edges of laponite with organic groups and the influence of this modification on gelation behavior. We compare three materials: an unmodified laponite, a laponite edge modified with a trimethyl moiety (MLap), and an octyldimethyl moiety (OLap). Gelation is investigated using rheology and NMR T-1 relaxation measurements and nuclear Overhauser enhancement spectroscopy (NOESY). MLap and OLap show qualitatively different gelation. Gelation of MLap is very similar to laponite: MLap gels over the same time scale as laponite and has about the same solid modulus, and the MLap gel is almost as transparent as laponite. In contrast, OLap gels rapidly relative to laponite and forms a weak, turbid gel. We believe that gelation in laponite and MLap results from the formation of a network of well-dispersed platelets (or a few platelets), while in OLap, gelation results from a network of stacks of several platelets. NMR relaxation measurements indicate that gelation does not affect the average relaxation of water protons. However, T, increases marginally for the protons in the organic moieties in MLap and decreases for protons in the organic moieties in OLap. Relaxation measurements, analyses of line width, and NOESY taken together suggest that, in OLap, gelation is a consequence of association of the organic moieties on the laponite edges, and that this association strengthens with time. Thus, the time-dependent changes in NMR suggest a structural origin for the time-dependent changes in the rheological behavior.

Pre-organization-mediated macrocylization: efficient synthesis and structural investigations of BINOL-m-phenylenediamine-derived macrocycles - Srinivas, Deekonda; Gonnade, Rajesh G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2008)
This letter describes a serendipitous discovery of an efficient synthetic route to BINOL-m-phenylenediamine-derived macrocycles. These macrocycles are quickly accessible in an one-pot procedure by the direct condensation of (R) and (S) BINOL bis-acids with suitably substituted m-phenylenediamine analogs. Structural investigations by single crystal X-ray crystallography and solution-state NMR studies provided convincing evidence of their intramolecular hydrogen bonding arrangement and rigid structural architecture. The striking feature of these macrocycles is their ready accessibility in optically pure form coupled with their ease of synthesis. (C) 2008 Elsevier Ltd. All rights reserved.

Rigid bicyclo[3.3.0]octane (octahydropentalene): a heavily constrained novel aliphatic template for molecular self-assembly - Kendhale, Amol M.; Gonnade, Rajesh G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2008)
This Letter reports the utility of a heavily constrained cis-fused bicyclo[3.3.0]octane (octahydropentalene) aliphatic template for effecting molecular self-assembly. An attractive feature of this system is its heavily constrained alicyclic backbone that would allow for the exploration of self-assembling systems with conformationally ordered features. (C) 2008 Elsevier Ltd. All rights reserved.

Sequence-specific unusual (1 -> 2)-type helical turns in alpha/beta-hybrid peptides - Prabhakaran, Panchami; Kale, Sangram S.; Puranik, Vedavati G.; Rajamohanan, P. R.; Chetina, Olga; Howard, Judith A. K.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Journal of the American Chemical Society, 2008)
This article describes novel conformationally ordered (alpha/beta-hybrid peptides consisting of repeating L-proline-anthranilic acid building blocks. These oligomers adopt a compact, right-handed helical architecture determined by the intrinsic conformational preferences of the individual amino acid residues. The striking feature of these oligomers is their ability to display an unusual periodic pseudo beta-turn network of nine-membered hydrogen-bonded rings formed in the forward direction of the sequence by 1–>2 amino acid interactions both in solid-state and in solution. Conformational investigations of several of these oligomers by single-crystal X-ray diffraction, solution-state NMR, and ab initio MO theory suggest that the characteristic steric and dihedral angle restraints exerted by proline are essential for stabilizing the unusual pseudo beta-turn network found in these oligomers. Replacing proline by the conformationally flexible analogue alanine (Ala) or by the conformationally more constrained alpha-amino isobutyric acid (Aib) had an adverse effect on the stabilization of this structural architecture. These findings increase the potential to design novel secondary structure elements profiting from the steric and dihedral angle constraints of the amino acid constituents and help to augment the conformational space available for synthetic oligomer design with diverse backbone structures.

Structural elucidation of propargylated products of 3-substituted-1,2,4-triazole-5-thiols by NMR techniques - Chaudhary, Preeti M.; Chavan, Sayalee R.; Kavitha, M.; Maybhate, Shailaja P.; Deshpande, Sunita R.; Likhite, Anjali P.; Rajamohanan, P. R. (Magnetic Resonance in Chemistry, 2008)
Propargylation of 3-substituted-1,2,4-triazole-5-thiols, which predominantly exist as their thione tautomers, was carried out with the view to synthesize different heterocycles and study their biological activity. Three different products namely, a mono S-propargyl and two S,N-dipropargyl regioisomers, arising from N1/N2 substitution, were isolated and characterized. Unambiguous structural elucidation of the regioisomers of S,N-dipropargyl derivatives was achieved by means of (13)C-(1)H HMBC technique. The proportion of the regioisomers was found to vary with the substituent on the 1,2,4-triazole thiols. No product corresponding to N4 substitution was isolated from any of the reactions carried out. Copyright (C) 2008 John Wiley & Sons, Ltd.
Keywords: (1)H NMR; (13)C NMR; (15)N NMR; 1; 2; 4-triazoles; HMBC; NMR; Regioisomers

Immobilization of phosphotungstic acid (PTA) on imidazole functionalized silica: evidence for the nature of PTA binding by solid state NMR and reaction studies - Sofia, L. T. Aany; Krishnan, Asha; Sankar, M.; Raj, N. K. Kala; Manikandan, Palanichamy; Rajamohanan, P. R.; Ajithkumar, Thalasseril G. (Journal of Physical Chemistry C, 2009)
Phosphotungstic acid (PTA) immobilized onto imidazole functionalized fumed silica and was used its an efficient catalyst for epoxidation of a variety of olefins using aqueous H(2)O(2) as all oxidant. Negligible leaching of PTA under the reaction conditions employed indicates a strong interaction between PTA and imidazole The immobilized catalysts Could be separated and reused after the catalytic cycle Evidence for the heterogenization of PTA oil the imidazole functionalized fumed silica has been inferred from different spectroscopic techniques like IR, UV-vis, and NMR. Importantly, the nature of binding of PTA oil the support has been studied in detail by solid state NMR spectroscopy using (15)N labeled imidazole Support. It is clear from the NMR Studies that the effective heterogenization of PTA is mainly due to imidazolium ion Formation oil the support by the acidic protons of PTA and the resultant ion pair

Incorporation of tin in different types of pores in SBA-15: synthesis, characterization and catalytic activity - Sasidharan, M.; Kiyozumi, Y.; Mal, N. K.; Paul, M.; Rajamohanan, P. R.; Bhaumik, Asim (Microporous and Mesoporous Materials, 2009)
Mesoporous Sn-SBA-15 has been synthesized by three different methods Such as conventional hydrothermal route, using cocatalyst NH4F and in the presence of organosilane precursor. All the materials are thoroughly characterized by powder X-ray diffraction (XRD), SEM. TEM. N-2 sorption and surface area measurements, diffuse-reflectance UV-visible and FTIR spectroscopy. TG-DTA and elemental analysis through ICP. Nitrogen adsorption data, XRD patterns, and TEM observations Suggests that the textural properties are retained during the isomorphous substitution of silicon by tin. ICP chemical analysis indicates that tin can be substituted in the range of S-l/S-n = 69-162. UV-visible spectra of samples synthesized by the cocatalytic approach exhibit unique absorption band at 213 nm characteristics of tin atom substituted in the smaller pores (2-3 nm) located inside the walls of mesopores. Further, an additional band at 224 nm can be assigned to Sri atoms located in the distorted tetrahedral position along the primary mesopores. In contrary, only one absorption band centered at 224 nm is observed for all the samples synthesized by conventional hydrothermal as well as in the presence of organosilane precursor. F-19 NMR spectra confirmed (no signal) the absence of occluded F- ions in the samples made with NH4F. Observed high catalytic activity in Baeyer-Villiger oxidation and Meerwin-Pondorf-Verly reduction under the liquid-phase conditions suggest the incorporation of a portion of tin in the smaller pores for the Sn-SBA-15 materials synthesized through cocatalyst method. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Baeyer-Villiger oxidation; catalysis; Functionalization of mesopores; Meerwin-Pondorf-Verly reduction; Sn-SBA-15

MgCl2 center dot 4(CH3)(2)CHOH: a new molecular adduct and super active polymerization catalyst support - Thushara, K. S.; Mathew, Renny; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Bhaduri, Sumit; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2009)
A new molecular adduct, MgCl(2 center dot)4(CH3)(2)CHOH, has been synthesized and characterized for structural aspects and demonstrated for super active ethylene polymerization activity with TiCl4 to ultrahigh molecular weight polyethylene in high yield.

Sterically controlled naphthalene homo-oligoamides with novel structural architectures - Prabhakaran, Panchami; Puranik, Vedavati G.; Chandran, Jima N.; Rajamohanan, P. R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2009)
Herein we report novel naphthalene homo-oligoamides, derived from 4-amino-3-methoxy-naphthalene-2-carboxylic acid and 4-amino-1-methoxy-naphthalene-2-carboxylic acid as monomer building blocks, that display an anti-periplanar arrangement of the naphthyl rings, primarily induced by steric interactions between adjacent groups and functionalities.

In situ encapsulation of pt nanoarchitectures of varying morphologies in mesoporous compounds - Prashar, Atul K.; Hodgkins, Robert P.; Chandran, Jima N.; Rajamohanan, P. R.; Devi, R. Nandini (Chemistry of Materials, 2010)
Nanoparticle morphology could be engineered and fine-tuned based on a novel in situ template method Different shapes of platinum nanoparticles were obtained from very low concentrations of precursors and could be isolated exclusively inside the mesochannels of SBA-15 This was achieved by dispersing a platinum precursor in surfactant modified polymer to different extents and using these composite materials as templates for the formation of mesoporous silica [PtCl(6)](2-) interacts with the cationic headgroup of the surfactant and facilitates the isolation of precursors within the composite template leading to the formation of nanoparticles molded by the walls of the mesochannels when calcined When this [PtCl(6)](2-)-surfactant-polymer micelle composite is aged for different duration, Pt nanoparticles of various morphologies like spheroids, nano rugby balls, and nanorods are obtained

Isolation, structure, and functional elucidation of a modified pentapeptide, cysteine protease inhibitor (CPI-2081) from streptomyces species 2081 that exhibit inhibitory effect on cancer cell migration - Singh, Jay Prakash; Tamang, Sudarsan; Rajamohanan, P. R.; Jima, N. C.; Chakraborty, Goutam; Kundu, Gopal C.; Gaikwad, Sushama M.; Khan, Mohammad Islam (Journal of Medicinal Chemistry, 2010)
Cysteine proteases play an important role in cell migration and tumor metastasis. Therefore, their inhibitors are of colossal interest, having potential to be developed as effective antimetastatic drugs for tumor chemotherapy. Traditionally, secondary metabolites from streptomyces show a wide range of diversity with respect to their biological activity and chemical nature. In this article, we have described the characterization of small molecule cysteine protease inhibitor, CPI-2081 (compound 1), a mixture of two novel pentapeptides, compound 1a (736.71 Da), and compound 1b (842.78 Da), isolated from Streptomyces species NCIM2081, following solvent extraction and repeated HPLC based on C18 chemistry, and completely characterized using a variety of both ID and 2D NMR spectroscopy. Further, it was found that nanomolar concentration of compound 1 is able to inhibit papain hydrolytic activity. Also, compound 1 significantly inhibits tumor cell migration at sub cytotoxic concentration, indicating its remarkable potential to be developed as antimetastatic drug, which will make chemotherapy more localized and specific, thereby minimizing the hazardous side effects on normal tissues.

New organic-inorganic hybrid microporous organosilica having high metal ion adsorption capacity - Paul, Manidipa; Pal, Nabanita; Rajamohanan, P. R.; Rana, Bharat S.; Sinha, Anil K.; Bhaumik, Asim (Physical Chemistry Chemical Physics, 2010)
A new microporous organic-inorganic hybrid organosilica LHMM-2 containing a bis(propyliminomethyl)benzene moiety inside the framework has been synthesized hydrothermally without using any template or structure-directing agent. Powder XRD and TEM image analyses suggest a new disordered microporous structure with pores of dimension ca. 0.54 nm, and C-13 and Si-29 MAS NMR and spectroscopic results indicate the presence of bridging organic bis(propyliminomethyl) benzene moiety in this framework. TPD-NH3 results suggested that nearly 5 times as much bis(propyliminomethyl) benzene moiety is located inside the micropore walls (matrix) than in the surface of the pores. LHMM-2 shows very high adsorption capacity for metal cations like Fe3+, Cu2+ and Zn2+.

Volume transition of PNIPAM in a nonionic surfactant hexagonal mesophase - Jijo, V. J.; Sharma, Kamendra P.; Mathew, Renny; Kamble, Samruddhi; Rajamohanan, P. R.; Ajithkumar, Thalasseril G.; Badiger, Manohar V.; Kumaraswamy, Guruswamy (Macromolecules, 2010)
We investigate the volume transition of a thermoresponsive polymer, poly(N-isopropylacrylamide), PNIPAM, in the presence of an aqueous solution of nonionic surfactant, C(12)E(9). We combine turbidimetry with optical microscopy, NMR, and SAXS to follow the volume transition of the PNIPAM and the H(1)-isotropic transition of the surfactant/water system. Nonionic surfactants such as C(12)E(9) are known to interact weakly with PNIPAM. Accordingly, we show that there is only a small change in the volume transition temperature for the PNIPAM in isotropic micellar solutions of C(12)E(9), even for relatively high concentrations of C(12)E(9). Interestingly, once the surfactant forms an H(1) phase, there is a dramatic decrease in the coil globule transition onset temperature. We believe that this behavior results from a competition between C(12)E(9) in the H(1) phase, and PNIPAM to associate with water. When PNIPAM in the H(1) phase is cooled to low enough temperatures so as to be in the coil state, it locally disturbs the hexagonal phase ordering. Thus, we show that for PNIPAM in a weakly interacting surfactant matrix, it is the phase behavior of the matrix rather than the matrix chemistry that governs the coil globule transition. Finally, we show that in a PNIPAM copolymer with a higher LCST we observe an interesting sequence of transitions in the surfactant phase: on cooling from a high temperature free-blowing turbid globular state (similar to 75 degrees C), we enter a free-flowing translucent coil phase (similar to 47 degrees C), then a turbid gel (similar to 25 degrees C) where the copolymer is collapsed in the HI phase, and finally a low-temperature clear gel (similar to 5 degrees C) where the copolymer is in the expanded coil state.

(-)-6 alpha-Hydroxy polyanthellin A - a novel antifouling diterpenoid from the Indian soft coral Cladiella krempfi (Hickson) - Mol, V. P. Limna; Raveendran, T. V.; Parameswaran, P. S.; Kunnath, R. J.; Rajamohanan, P. R. (Canadian Journal of Chemistry-Revue Canadienne De Chimie, 2011)
Bioassay-guided purification of methanol extract of the soft coral Cladiella krempfi (Octocorallia: Alcynocea) yielded a novel eunicellin-type diterpenoid, (-)-6 alpha-hydroxy polyanthellin A (1), active against the cyprids of the fouling barnacle, Balanus amphitrite (EC(50) 9.02 mu g/mL; LC(50) 36 mu g/mL; and therapeutic ratio = 4). The structure of compound 1 was determined from its spectral data, including IR, NMR (1D and 2D NMR), and mass spectra.
Keywords: antifouling; Balanus amphitrite; biofouling; Cladiella krempfi; diterpenes

Assembly of polyethyleneimine in the hexagonal mesophase of nonionic surfactant: effect of pH and temperature - Sharma, Kamendra P.; Choudhury, Chandan Kumar; Srivastava, Sonal; Davis, Hilda C.; Rajamohanan, P. R.; Roy, Sudip; Kumaraswamy, Guruswamy (Journal of Physical Chemistry B, 2011)
We investigate the dispersion of a pH responsive polymer, polyethyleneimine, PEI, in a hexagonal (H(1)) mesophase of a nonionic surfactant, C(12)E(9), and water, at pH ranging from basic (pH = 12.8) to acidic (pH = 1). While the C(12)E(9)/H(2)O phase behavior is independent of pH, we demonstrate that, in the PEI/C(12)E(9)/H(2)O system, changing the pH influences PEI-C(12)E(9) interactions, and thus, influences the isotropic-H(1) phase transition. With decrease in pH, there is increasing protonation of the PEI chain, and consequently, the chain extends. We show, using a combination of SAXs, optical microscopy and visual experiments, that the inclusion of PEI in a 1:1 surfactant water mixture, lowers the hexagonal-isotropic transition temperature, T. At higher pH = 12.8 T(HI) shows a pronounced decrease from SO to 13 degrees C on addition of PEI, and the PEI/C(12)E(9)/H(2)O system forms a transparent gel. At pH = 1, we observe qualitatively different behavior and an opaque gel forms below T(HI)= 25 degrees C. The isotropic-H(1) transition, in turn, influences the phase separation of PEI chains from the C(12)E(9)/H(2)O system. 2D NMR ROESY data provides evidence that there are strong surfactant PEI interactions at high pH that significantly reduce at lower pH. The NMR data is in accord with molecular dynamics simulations that show that surfactants strongly aggregate with unprotonated PEI chains, but not with fully protonated chains; thus, in this system, the pH controls a cascade of microstructural organization: increasing pH decreases chain protonation and increases polymer-surfactant interactions, resulting in suppression of the isotropic-H(1) transition to lower temperatures, thus, influencing the phase separation of PEI from the surfactant/water system.

Effect of tethering on the structure-property relationship of TPU-dual modified laponite clay nanocomposites prepared by ex-situ and in-situ techniques - Mishra, Ananta K.; Chattopadhyay, Santanu; Rajamohanan, P. R.; Nando, Golok B. (Polymer, 2011)
Novel Thermoplastic Polyurethane (TPU)-dual modified Laponite clay nanocomposites were prepared by ex-situ and in-situ techniques. Two types of modified clays used in this work differ from each other by the number of active functional groups (tethering). Modified nanoclays are characterized by FTIR, Solid State NMR, XRD and TGA. Structural differences in the modified clays lead to novel tubular, elliptical and spherically aggregated morphologies of clays together with the hard segments of TPU. Changes in such morphology result in the difference in segmental relaxation, mechanical and rheological properties of the nanocomposites. In-situ prepared nanocomposites register inferior properties as compared to their ex-situ counterparts. The percent improvement in tensile strength and elongation at break of the ex-situ prepared nanocomposites with the modified clay having lesser tethering are found to be 67% and 208%, respectively. Thermal stability is enhanced by 35 degrees C as compared to that of the neat TPU. (C) 2010 Published by Elsevier Ltd.
Keywords: Dual modification; Nanocomposites; Thermoplastic polyurethane

In situ encapsulation of Pt nanoparticles in mesoporous silica: synthesis, characterisation and effect of particle size on CO oxidation - Prashar, Atul K.; Mayadevi, S.; Rajamohanan, P. R.; Devi, R. Nandini (Applied Catalysis A-General, 2011)
Pt nanoparticles of narrow size distribution and average particle size of 4.4 nm are isolated exclusively inside SBA-12 mesoporous silica by a novel in situ method. The interaction of Pt precursor with surfactant-polymer composite micelle is followed by NMR and UV studies. The final Pt incorporated silica material is characterised by XRD, TEM and N(2) adsorption. The mesoporous nature of the silica is found to be intact after Pt incorporation without any pore blockage. CO oxidation activity of this material is compared with that of mesoporous silica incorporating different sizes of Pt viz., 1.8, 3.6 and 8 nm. Activation energies of CO oxidation for all these materials are calculated by a simple differential method based on first principles. A comparison of activation energies and single site yields reveals that these parameters are distinguishably less in catalyst containing 1.8 nm Pt nanoparticles but more or less same in catalysts containing 3.6, 4.4 and 8 nm Pt nanoparticles. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: CO oxidation; In situ synthesis; Mesoporous silica; Pt nanoparticle

MgCl2 center dot 6PhCH(2)OH - a new molecular adduct as support material for ziegler-natta catalyst: synthesis, characterization and catalytic activity - Gnanakumar, Edwin S.; Thushara, K. S.; Bhange, Deu S.; Mathew, Renny; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Bhaduri, Sumit; Gopinath, Chinnakonda S. (Dalton Transactions, 2011)
Benzyl alcohol has been used to prepare a single phase MgCl2 center dot 6BzOH molecular adduct as a support for an ethylene polymerization catalyst (Ziegler catalyst). The structural, spectroscopic and morphological aspects of the MgCl2 center dot 6BzOH molecular adduct and the Ziegler catalyst have been thoroughly studied by various physicochemical characterization techniques. The presence of MgO6 octahedrons due to the interaction of Mg2+ with six -OH groups of the benzyl alcohol is confirmed from a Raman feature at 703 cm(-1), and structural studies. The supported catalyst activity has been evaluated for the ethylene polymerization reaction. The lower polymerization activity of the titanated Ziegler-Natta catalyst compared with a standard catalyst is attributed to the strong interaction of titanium chloride with the support and associated electronic factors.

Structure-property of thermoplastic polyurethane-clay nanocomposite based on covalent and dual-modified laponite - Mishra, Ananta K.; Rajamohanan, P. R.; Nando, Golok B.; Chattopadhyay, Santanu (Journal of Computational and Theoretical Nanoscience, 2011)
Modification of surface of clay platelets by ionic and covalent modification techniques renders it to be easily dispersed in polymers like, Thermoplastic Polyurethane (TPU). Only ionic or covalent modification techniques in isolation are not sufficient to achieve uniform nanoscale dispersion of Laponite (synthetic hectorite nanoclay) in TPU. Hence, the dual modification of Laponite (both ionic and covalent) is performed and the effects of the modification on the morphology, thermal and rheological behaviors of the TPU-modified clay nanocomposites have been studied. The degree of exfoliation of clay platelet in TPU matrix is found to be higher for dual functionalized nanoclays compared to their singly modified counterparts. Interestingly, dual modified Laponite clays prepared by using two different techniques (ionic followed by covalent and covalent followed by ionic) exhibit different morphology and properties. The dual modified clays significantly alter the equilibrium morphology of TPU. The storage modulus of the dual modified Laponite-TPU nanocomposite in the glassy region (at -60 degrees C) land in the rubbery region (+98 degrees C) is improved by 172.8% and 85%, respectively as compared to the neat TPU. Similarly, the onset of degradation is found to be enhanced by 28.7 degrees C as compared to the neat TPU.
Keywords: Dual modification; Laponite Nanocomposite; Morphology; Structure-Property; Thermoplastic polyurethane

Toward an understanding of the molecular level properties of ziegler-natta catalyst support with and without the internal electron donor - Thushara, K. S.; Gnanakumar, Edwin S.; Mathew, Renny; Jha, Ratnesh Kumar; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Sarma, Krishna; Padmanabhan, Sudhakar; Bhaduri, Sumit; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2011)
Two Ziegler-Natta catalysts supported on molecular adducts, namely, MgCl2 center dot 6EtOH (ME) and MgCl2 center dot 5EtOH center dot EtOOCPh (Est-ME), have been prepared. A systematic effort has been made to unravel the molecular level structure property relationships of the catalysts and adducts. Ethylbenzoate is an internal electron donor, and its in situ formation through EtOH+PhCOCl coupling is successfully achieved. The above adduct has been treated with TiCl4, and the resultant catalyst (Ti/Est-ME) is evaluated for ethylene polymerization activity. Rand C-13 CP/MAS NMR of Est-ME (Ti/Est-ME) show carbonyl features at 1730 (1680) cm(-1) and 169 (170) delta, respectively, providing direct support for the presence of ester as an integral part. In spite of low surface area, Ti/Est-ME gives higher yield for ethylene polymerization than the one derived from ME. The results indicate that electronic environment is more important than surface area or any other single factor in determining the polymerization activity.

Conformational modulation of Ant-Pro oligomers using chirality alteration of proline residues - Kale, Sangram S.; Kotmale, Amol S.; Dutta, Achintya Kumar; Pal, Sourav; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2012)
Structural modulation of Ant-Pro (anthranilic acid-proline) oligomers has been carried out by chirality alteration of the proline residues. The results suggest that the chirality altered oligomers show well-defined helical conformation featuring nine-membered hydrogen bonding interactions - without compromising conformational rigidity.

Discovering bisdemethoxycurcumin from curcuma longa rhizome as a potent small molecule inhibitor of human pancreatic alpha-amylase, a target for type-2 diabetes - Ponnusamy, Sudha; Smita S. Zinjarde; Bhargava, Shobha; Rajamohanan, P. R.; RaviKumar, Ameeta (Food Chemistry, 2012)
Curcuma longa rhizome is used extensively in culinary preparations in Far East and South-East Asia. Health benefits of curcuminoids from C. longa as antioxidants, anti-cancer and anti-inflammatory molecules have been well documented. We report here for the first time that Bisdemethoxycurcumin (BDMC) from C. longa, acts as an inhibitor to inactivate human pancreatic alpha-amylase, a therapeutic target for oral hypoglycemic agents in type-2 diabetes. Bioactivity guided isolation of rhizome isopropanol extract led to the identification by HPLC and NMR of BDMC as a lead small molecule inhibitor of porcine and human pancreatic alpha-amylase with an IC50 value of 0.026 and 0.025 mM, respectively. Kinetic analysis revealed that using starch as the substrate, HPA exhibited an uncompetitive mode of inhibition with an apparent K-i of 3.0 mu M. The study gains importance as BDMC could be a good drug candidate in development of new inhibitors of HPA and of functional foods for controlling starch digestion in order to reduce post-prandial hyperglycemia. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: BDMC; Curcuma longa; Human pancreatic amylase; kinetics; Type-2 diabetes

Expanding the structural repertoire of beta/alpha Ant-Pro (anthranilic acid-proline) oligomers into gamma/alpha 2-Amb-Pro (2-aminomethyl benzoic acid-proline) oligomers - Ramesh, Veera V. E.; Priya, Gowri; Rajamohanan, P. R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Tetrahedron, 2012)
In this article, we report a novel class of heterogeneous synthetic oligomers featuring the conformationally constrained amino acid residues - 2-aminomethyl benzoic acid (2-Amb) and proline (Pro) in repeating sequences. Oligomers as large as hexadecamers featuring the conformationally restricted gamma/alpha 2-Amb-Pro motif have been assembled using solution-phase Boc strategy, following multi-step synthetic sequences starting from the commercially available O-toluic acid. EDC-mediated peptide coupling has been found to be optimum for the assembly of the relatively non-polar oligomers, which could be readily purified by the standard column chromatographic purification procedures. This study offers considerable prospects of expanding the structural repertoire of beta/alpha Ant-Pro motif, which has been described earlier to assume right-handed helical architecture displaying robust nine-membered-ring closed network of hydrogen-bonding interactions, into gamma/alpha 2-Amb-Pro motif. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Amino acids; Foldamer; Peptides; Proline; Synthetic oligomers

Lamellar melting, not crystal motion, results in softening of polyoxymethylene on heating - Kumaraswamy, Guruswamy; Surve, Nikita S.; Mathew, Renny; Rana, Abhimanyu; Jha, Saroj K.; Bulakh, Neelima N.; Nisal, Anuya; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Ratnagiri, Ram (Macromolecules, 2012)
We probe temperature-dependent changes in the semicrystalline microstructure of polyoxymethylene using a combination of modulated DSC, SAXS, and solid-state NMR to characterize macroscopic behavior, lamellar-level structure, and molecular environments, respectively, and correlate these with the change in mechanical properties probed using DMA and AFM. Two model samples are investigated: a melt crystallized sample prepared by injection molding and a sample obtained by crystallization from dilute solution. Our investigations reveal that, for both samples, there is an increase in crystalline motions and in the amorphous content on heating. DMA and AFM measurements reveal that the modulus of the molded sample decreases on heating to about 100 degrees C; however, there is a significant difference in behavior of the solution crystals, where we observe no significant decrease in stiffness (from AFM measurements). Thus, in contrast to previous reports, we demonstrate that the decrease in modulus on heating polyoxymethylene does not correlate with chain motions in the crystalline regions. We use SAXS to probe the semicrystalline morphology for the samples on heating and show that, for the molded sample, there is a distribution of lamellar thickness at room temperature and that the thin lamellae in this distribution melt on heating. In contrast to the behavior of the melt crystallized samples, the solution crystals exhibit no change in the lamellar stacking on heating to 150 degrees C. We also demonstrate that, on heating, the amorphous regions in the solution crystals always appear to have restricted mobility while there are mobile and low mobility amorphous regions in the molded samples. Our results suggest that, contrary to conventional belief, the decrease in modulus on heating polyoxymethylene arises not from motions in the crystalline lamellae but primarily from melting of thin lamellae.

MgCl2 center dot 4((CH3)(2)CHCH2OH): a new molecular adduct for the preparation of TiClx/MgCl2 catalyst for olefin polymerization - Thushara, K. S.; Gnanakumar, Edwin S.; Mathew, Renny; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Bhaduri, Sumit; Gopinath, Chinnakonda S. (Dalton Transactions, 2012)
A new molecular adduct of MgCl2 with isobutanol, namely MgCl2 center dot 4((CH3)(2)CHCH2OH) (MgiBOH), has been prepared as a precursor to the supporting material for an olefin polymerization catalyst. The MgiBOH adduct and final titanated Ziegler-Natta catalysts have been thoroughly characterized by powder XRD, thermal analysis, Raman spectroscopy and solid-state NMR for structural and spectroscopy aspects. A peak observed at 712 cm(-1) in the Raman spectra of MgiBOH indicates the characteristic Mg-O-6 breathing mode and the formation of the adduct. The diffraction feature at 2 theta = 7.8 degrees (d = 11.223 angstrom) in the XRD confirms the adduct formation and the layered structure. The aim of the present article is to study how the insertion of a bulky isobutanol moiety affects the structural and electronic properties of the MgCl2 isobutanol molecular adduct. Indeed, the focus of the present study is to explore how the presence of isobutanol, in the initial molecular adduct, influences the final Z-N catalyst properties and its activity.

MgCl2 center dot 6C(6)H(11)OH: a high mileage porous support for ziegler-natta catalyst - Gnanakumar, Edwin S.; Thushara, K. S.; Gowda, Ravikumar R.; Raman, Sumesh K.; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Chakraborty, Debashis; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2012)
A new and single phase molecular adduct of MgCl2 with six cyclohexanol molecules MgCl2 center dot 6C(6)H(11)OH (MgCyOH) has been synthesized. Structural insight to this adduct was obtained by a variety of physicochemical methods. C-13 CPMAS spectrum and single pulse MAS spectra with high power proton decoupling recorded at different relaxation time showed the presence of two different sets of magnetically unequal cylcohexanol molecules present around Mg2+. A Raman feature of MgCyOH at 712 cm(-1) confirms that cylcohexanol molecules are present around Mg2+ in an octahedral environment. MgCyOH has been used as support material to prepare Ziegler-Natta (Z-N) active catalyst. Textural property of above Z-N catalyst exhibits high surface area (236 m(2)/g) with high porosity. Above active catalyst has been screened for ethylene polymerization. Depending on the cocatalyst employed (Me3Al, Et3Al, and iso-Bu3Al) and ethylene pressure, polyethylene yield varies an order of magnitude, from 378 to 3570 g/g catalyst, indicating a possible creation of different active sites and different interaction between cocatalyst and catalyst.

Biodegradation of phenol by the yeast candida tropicalis: an investigation by NMR spectroscopy - Phalgune, U. D.; Rajamohanan, P. R.; Gaikwad, B. G.; Varma, R. J.; George, S. (Applied Biochemistry and Biotechnology, 2013)
The process of phenol biodegradation by the yeast Candida tropicalis NCIM 3556 in aqueous medium was studied by H-1, C-13, and DOSY NMR techniques. Samples at regular intervals were centrifuged to separate the cells, and H-1 spectral data were collected at 400 MHz. Though a gradual decrease in the concentration of phenol was observed, after an incubation period of similar to 8 h, formation of any intermediate products could not be detected. Experiments carried out with uniformly C-13-labeled phenol also failed to detect formation of any carboxylic acid intermediates during degradation. The studies indicated that the phenol was completely degraded to carbon dioxide and water in approximately 20 h. Self-diffusion coefficient measurements showed that the lifetime of phenol in the bound form is too small to impart any change in its diffusion behavior and the intermediates formed are converted to carbon dioxide and water at a very fast rate.
Keywords: biocatalysis; Carboxylic acid; Diffusion; Enzyme; NMR spectroscopy; phenol

Carboxamide versus sulfonamide in peptide backbone folding: a case study with a hetero foldamer - Ramesh, Veera V. E.; Kale, Sangram S.; Kotmale, Amol S.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Organic Letters, 2013)
Strikingly dissimilar hydrogen-bonding patterns have been observed for two sets of closely similar hetero foldamers containing carboxamide and sulfonamides at regular intervals. Although both foldamers maintain conformational ordering, the hydrogen-bonding pattern and backbone helical handedness differ diametrically.

Design, synthesis, structural characterization by IR, 1H, 13C, 15N, 2D-NMR, X-ray diffraction and evaluation of a new class of phenylaminoacetic acid benzylidene hydrazines as pfENR inhibitors - Samal, Ramanuj P.; Khedkar, Vijay M.; Pissurlenkar, Raghuvir R. S.; Bwalya, Angela Gono; Tasdemir, Deniz; Joshi, Ramesh A.; Rajamohanan, P. R.; Puranik, Vedavati G.; Coutinho, Evans C. (Chemical Biology & Drug Design, 2013)
Recent studies have revealed that plasmodial enoyl-ACP reductase (pfENR, FabI), one of the crucial enzymes in the plasmodial type II fatty acid synthesis II (FAS II) pathway, is a promising target for liver stage malaria infections. Hence, pfENR inhibitors have the potential to be used as causal malarial prophylactic agents. In this study, we report the design, synthesis, structural characterization and evaluation of a new class of pfENR inhibitors. The search for inhibitors began with a virtual screen of the iResearch database by molecular docking. Hits obtained from the virtual screen were ranked according to their Glide score. One hit was selected as a lead and modified to improve its binding to pfENR; from this, a series of phenylamino acetic acid benzylidene hydrazides were designed and synthesized. These molecules were thoroughly characterized by IR, 1H, 13C, 15N, 2D-NMR (COSY, NOESY, 1H-13C, 1H-15N HSQC and HMBC), and X-ray diffraction. NMR studies revealed the existence of conformational/configurational isomers around the amide and imine functionalities. The major species in DMSO solution is the E, E form, which is in dynamic equilibrium with the Z, E isomer. In the solid state, the molecule has a completely extended conformation and forms helical structures that are stabilized by strong hydrogen bond interactions, forming a helical structure stabilized by N-H...O interactions, a feature unique to this class of compounds. Furthermore, detailed investigation of the NMR spectra indicated the presence of a minor impurity in most compounds. The structure of this impurity was deduced as an imidazoline-4-one derivative based on 1H-13C and 1H-15H HMBC spectra and was confirmed from the NOESY spectra. The molecules were screened for in vitro activity against recombinant pfENR enzyme by a spectrophotometric assay. Four molecules, viz. 17, 7, 10, and 12 were found to be active at 7, 8, 10, and 12m concentration, respectively, showing promising pfENR inhibitory potential. A classification model was derived based on a binary QSAR approach termed recursive partitioning (RP) to highlight structural characteristics that could be tuned to improve activity.
Keywords: ADMET; docking; enoyl-ACP reductase; FabI; hydrogen bonding; NMR; phenylaminoacetic acid benzylidene hydrazine; Plasmodium falciparum; Plasmodium falciparum enoyl-ACP reductase; QSAR; recursive partitioning; X-ray diffraction

GIAO/DFT studies on 1,2,4-triazole-5-thiones and their propargyl derivatives - Phalgune, Usha D.; Vanka, Kumar; Rajamohanan, P. R. (Magnetic Resonance in Chemistry, 2013)
Density functional theory (DFT)/Becke-Lee-Yang-Parr (B3LYP) and gauge-including atomic orbital (GIAO) calculations were performed on a number of 1,2,4-triazole derivatives, and the optimized structural parameters were employed to ascertain the nature of their predominant tautomers. C-13 and N-15 NMR chemical shifts of 3-substituted 1,2,4-triazole-5-thiones and their propargylated derivatives were calculated via GIAO/DFT approach at the B3LYP level of theory with geometry optimization using a 6-311++G** basis set. A good agreement between theoretical and experimental C-13 and N-15 NMR chemical shifts could be found for the systems investigated. The data generated were useful in predicting N-15 chemical shifts of all the nitrogen atoms of the triazole ring, some of which could not be obtained in solution state N-15 HMBC/HSQC NMR measurements. The energy profile computed for the dipropargylated derivatives was found to follow the product distribution profile of regioisomers formed during propargylation of 1,2,4-triazole thiones. Copyright (c) 2013 John Wiley & Sons, Ltd.
Keywords: 1; 2; 4-triazole-5-thiones; C-13; DFT; GIAO; N-15; NMR; Regioisomers; tautomers

MgCl2 center dot 6CH(3)OH: a simple molecular adduct and its influence as a porous support for olefin polymerization - Gnanakumar, Edwin S.; Gowda, Ravikumar R.; Kunjir, Shrikant; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Chakraborty, Debashis; Gopinath, Chinnakonda S. (ACS Catalysis, 2013)
A single phase molecular adduct, MgCl2 center dot 6CH(3)OH has been synthesized using MgCl2 and the simplest alcohol, methanol. Structural, spectroscopic, and morphological studies have been carried out for a better understanding of the single phase MgCl2 center dot 6CH(3)OH adduct. C-13 CPMAS solid state NMR studies show all six methanol molecules are magnetically equivalent and present in a single environment around the Mg2+ center. Raman spectral analysis of the characteristic peak at 708 cm(-1) substantiates octahedral coordination of six CH3OH molecules around Mg2+. Solid state C-13 NMR measurements, made after heat treatment at different temperatures, have been utilized to understand the variations in CH3OH stoichiometry and coordination around Mg2+ with temperature. A titanated active catalyst, TiCl4 on MgCl2 center dot 6CH(3)OH, has also been synthesized and subjected to detailed characterizations. The active catalyst shows high surface area (102 m(2)/g) and mesoporosity. The titanated catalyst has been screened for ethylene polymerization reactions using different cocatalysts (R3Al; R= -CH3, -CH2CH3, and -CH2CH(CH3)(2)). A total of 7.25 kg of polyethylene per gram of catalyst has been obtained with Me3Al cocatalyst, which is six times higher in activity compared with commercial Me3Al/TiCl4/MgCl2 center dot 6EtOH-supported orted catalystAlthough porosity influences the catalytic activity, other factors also seem to contribute to the total catalytic activity.
Keywords: heterogeneous catalysis; MgCl2; Molecular adduct; olefin polymerization; Ziegler-Natta catalyst

Orthanilic acid-promoted reverse turn formation in peptides - Kale, Sangram S.; Priya, Gowri; Kotmale, Amol S.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Chemical Communications, 2013)
Orthanilic acid (2-aminobenzenesulfonic acid, (S)Ant), an aromatic beta-amino acid, has been shown to be highly useful in inducing a folded conformation in peptides. When incorporated into peptide sequences (Xaa-(S)Ant-Yaa), this rigid aromatic beta-amino acid strongly imparts a reverse-turn conformation to the peptide backbone, featuring robust 11-membered-ring hydrogen-bonding.

9-Fluorenemethanol: an internal electron donor to fine tune olefin polymerization activity - Gnanakumar, Edwin S.; Chokkapu, Eswara Rao; Kunjir, Shrikant; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Chakraborty, Debashis; Gopinath, Chinnakonda S. (Dalton Transactions, 2014)
A new MgCl2 based molecular adduct has been synthesized with 9-fluorenemethanol (9FM) as a novel internal electron donor (IED), along with ethanol (EtOH) (MgCl2 center dot n9FM center dot xEtOH). The above molecular adduct has been subjected to a variety of structural, spectroscopic and morphological characterization techniques. The results of the solid state C-13 CPMAS NMR technique suggests the coordination of 9FM to MgCl2. Observation of a low angle diffraction peak at 2 theta = 5.7 degrees (d = 15.5 angstrom) underscores the coordination of 9FM along the z-axis, and ethanol in the molecular adduct. Active Ziegler-Natta catalysts were prepared by two different synthesis methods; the conventional method to obtain a high surface area active catalyst, and other one with 9FM as an integral part of the active catalyst in order to study the influence of 9FM as an IED over the active sites. The active catalysts were also characterized thoroughly with different analytical tools. The XRD results show (003) facets of delta-MgCl2 (alpha-MgCl2) for the conventional (non-conventional) titanated catalyst. Results of the ethylene polymerization activity study reveals that the conventionally prepared highly porous active catalyst shows 1.7-2.5 times higher activity than the non-conventional prepared catalyst; however, the latter shows a low molecular weight distribution and confirms the role of the Lewis base as an IED.

Comparison of sodium zirconium phosphate and calcium zirconium phosphate structures for the retention of fluoride - Dey, Ambarish; Das Gupta, Amit; Basu, Debrata; Ambashta, Ritu D.; Wattal, P. K.; Kumar, Sanjiv; Body, Monique; Rajamohanan, P. R. (Journal of Radioanalytical and Nuclear Chemistry, 2014)
Fluoride anion interaction has been explored for the first time to investigate how the structure of sodium zirconium phosphate (NZP) and calcium zirconium phosphate (CZP) can be altered in its presence. Different compositions were made by adding NaF and CaF2 in CZP and NZP matrices respectively. Fluoride interaction differs with NZP and CZP structure as suggested by F-NMR data. The addition of fluoride to the NZP or CZP structure enables to stabilize the structure at a low temperature of 600-700 A degrees C under microwave conditions.
Keywords: F-NMR; Fluoride characterization; Microwave; NZP; PIGE

Conformational modulation of peptide secondary structures using beta-aminobenzenesulfonic acid - Kale, Sangram S.; Kunjir, Shrikant M.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Chemical Communications, 2014)
This communication describes the influence of beta-aminobenzenesulfonic acid ((S)Ant) on the conformational preferences of hetero foldamers. The designed (Aib-(S)Ant-Aib)(n) and (Aib-(S)Ant-Pro)(n) oligomers display a well-defined folded conformation featuring intramolecular mixed hydrogen bonding (7/11) and intra-residual (6/5) H-bonding interactions, respectively.

Functional isoDNA aptamers: modified thrombin binding aptamers with a 2'-5'-linked sugarphosphate backbone (isoTBA) - Gunjal, Anita D.; Fernandes, Moneesha; Erande, Namrata D.; Rajamohanan, P. R.; Kumar, Vaijayanti A. (Chemical Communications, 2014)
The regioisomeric 3'-deoxy-2'-5'-linked thrombin binding DNA aptamers (isoTBAs) were chemically synthesized and their ability to form unimolecular anti-parallel G-quadruplexes in the presence of K+ ions was evaluated. These modified sequences retain the function of the native thrombin binding aptamer (TBA), exhibit better stability against exonuclease and are capable of slowing down the process of blood clotting.

Isolation, characterization and antihyperlipidemic activity of secoisolariciresinol diglucoside in poloxamer-407-induced experimental hyperlipidemia - Zanwar, Anand A.; Hegde, Mahabaleshwar V.; Rojatkar, Supada R.; Sonawane, Kiran B.; Rajamohanan, P. R.; Bodhankar, Subhash L. (Pharmaceutical Biology, 2014)
Context: Linum usitatissimum L. (Linaceae), commonly known as flaxseed, is a good source of dietary fiber and lignans. Earlier we reported cardioprotective, antihyperlipidemic, and in vitro antioxidant activity of flax lignan concentrate (FLC) obtained from flaxseed. Objectives: To isolate secoisolariciresinol diglucoside (SDG) from FLC and to evaluate the antihyperlipidemic activity of SDG in poloxamer-407 (P-407)-induced hyperlipidaemic mice. Material and methods: FLC was subjected to column chromatography and further subjected to preparative HPTLC to isolate SDG. The chemical structure of the isolated compound was elucidated by UV, IR, H-1 NMR, C-13 NMR, DEPT, COSY, HSQC, HMBC, ROESY, MS, and specific optical rotation was recorded. Further, we have investigated the antihyperlipidaemic effect of SDG (20 mg/kg) in P-407-induced hyperlipidaemic rats. Hyperlipidaemia was induced by intraperitoneal administration of P-407 (30% w/v). Serum lipid parameters such as total cholesterol (TC), triglycerides (TG), and high-density lipoprotein cholesterol (HDL-C) levels were measured. Results and discussion: The structure and stereochemistry of the isolated compound were confirmed on the basis of 1D and 2D spectral data and characterized as SDG. Finally, isolated pure SDG was screened using a P-407-induced mice model for its antihyperlipidemic action using serum lipid parameters. The isolated SDG (20 mg/kg) significantly reduced serum cholesterol, triglyceride (p<0.001), very low-density lipoprotein (p<0.05), and non-significantly increased HDL-C. Conclusion: Finally, it was concluded unequivocally that SDG showed antihyperlipidaemic effects in P-407-induced hyperlipidaemic mice. Isolated pure SDG confirms that SDG is beneficial in the prevention of experimental hyperlipidemia in laboratory animals.
Keywords: column chromatography; flaxseed; Linum usitatissimum

Probing the folding induction ability of orthanilic acid in peptides: some observations - Roy, Arup; Kotmale, Amol S.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (RSC Advances, 2014)
This paper describes the ability of orthanilic acid (2-aminobenzenesulfonic acid, (S)Ant) to promote folding when introduced in a peptide sequence. Three peptide sequences, containing orthanilic acid (SAnt) with a sulfonamide moiety in the turn segment, have been synthesized in the solution phase using suitable coupling agents, and their structural aspects investigated using NMR and X-ray crystallographic studies. Solid- and solution-state conformational analyses reveal that the peptide sequences containing orthanilic acid in their backbone exist in a folded conformation featuring long-range 15-membered ring H-bonding.

Solid-state NMR investigations of a MgCl2 center dot 4(CH3)(2)CHCH2OH molecular adduct: a peculiar case of reversible equilibrium between two phases - Thushara, K. S.; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Gopinath, Chinnakonda S. (Journal of Physical Chemistry A, 2014)
MgCl2 center dot xROH molecular adducts are extensively employed as a support material for Ziegler-Natta polyolefin catalysis. However, their structural properties are not well understood. Recently, we reported on the preparation of an isobutanol adduct, MgCl2 center dot 4(CH3)(2)CHCH2OH (MgiBuOH) (Dalton Trans. 2012, 41, 11311), which is very sensitive to the preparation conditions, such as the temperature and refluxing time. For the present study, the structural properties of MgiBuOH adducts prepared under different conditions have been investigated thoroughly by solid-state NMR and nonambient XRD. Formation of two phases has been confirmed, and in situ variable temperature solid-state NMR measurements confirm the coexistence of two phases as well as the oscillation from one to another phase. It is expected that such molecular adducts could have a significant role in organic transformation reactions due to an oscillating structural component. An understanding of phase oscillation with the Mg2+ ion as the central metal ion might shed some light toward understanding various biological and structural functions.

Structural investigations of porous MgCl2-2-butanol molecular adduct as support for olefin polymerization - Thushara, K. S.; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Gopinath, Chinnakonda S. (Applied Catalysis A-General, 2014)
A new heterogeneous Ziegler-Natta (Z-N) catalyst support material, MgCl2 center dot 4(CH3CH(OH)CH2CH3) (Mg2BuOH) has been synthesized. 2-Butanol, a linear, secondary alcohol was chosen for the generation of an active MgCl2 support which results in a Z-N catalyst with TiCl4. Significant feature of this work is the formation of rod shaped molecular adduct with highly porous character. Adduct material is characterized by XRD, TG-DTA, Raman spectroscopy, solid-state NMR and SEM. Activity of the Z-N catalyst supported on Mg2BuOH for ethylene polymerization is comparable with that of commercially available heterogeneous Z-N catalyst. However, there is scope to improve the activity by optimizing textural properties. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: heterogeneous catalysis; MgCl2; Molecular adduct; NMR; Polyolefin; Ziegler-Natta catalyst

Unexpected observations during the total synthesis of calothrixin B-sodium methoxide as a source of hydride - Bhosale, Shrikar M.; Momin, Aadil A.; Kunjir, Shrikant; Rajamohanan, P. R.; Kusurkar, Radhika S. (Tetrahedron Letters, 2014)
During the total synthesis of calothrixin B, various novel and unexpected results were noticed such as cleavage of C-N bond in imine using sodium cyanoborohydride, sodium methoxide as a hydride source for reduction, deformylation in the presence of bromine, and deacylation using ceric ammonium nitrate (CAN). A detailed mechanism has been proposed for the unexpected results and a few of them are generalized. Temperature dependent NMR studies have been carried out for confirmation of the structure of one of the intermediates in the synthetic sequence. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Azoxybenzene; Calothrixin B; reduction; Sodium cyanoborohydride; Sodium methoxide

Experimental signature of microheterogeneity in ionic liquid-H2O systems and their perturbation by adding Li+ salts: a pulsed gradient spin-echo NMR approach - Nanda, Raju; Rajamohanan, P. R.; Kumar, Anil (Chemphyschem, 2015)
Distinct microheterogeneity has been observed in the [OMIM]Br-H2O system, which is interestingly perturbed by the addition of Li+ salts, indicating unusual diffusivity of [OMIM]Br and H2O molecules. However, the diffusional dynamics of water clusters show contrasting salting behavior at higher concentrations of Li+ salts, following the classical salting phenomenon in lower amounts. In contrast, the existing microheterogeneity in the [BMIM]Br-H2O system is weak enough to show any perturbation caused by the Li+ salts on the NMR time scale.
Keywords: ionic liquids; lithium; microheterogeneity; salt effect; viscosity

Insertion copolymerization of difunctional polar vinyl monomers with ethylene - Gaikwad, Shahaji R.; Deshmukh, Satej S.; Gonnade, Rajesh G.; Rajamohanan, P. R.; Chikkali, Samir H. (ACS Macro Letters, 2015)
A single-step synthesis, structural characterization and application of a neutral, acetonitrile ligated, palladium-phosphinesulfonate complex [{P<\^>O}PdMe(L)] (P<\^>O = K-2-P,O Ar2PC6H4SO2O with Ar = 2-MeOC6H4; L = CH3CN) (3) in coordination/insertion copolymerization of ethylene with difunctional olefin is investigated. In a significant development, complex 3 was found to catalyze insertion copolymerization of industrially relevant 1,1-disubstituted difunctional vinyl monomers for the first time. Thus, insertion copolymerization of ethyl-2-cyanoacrylate (ECA or super glue) and trifluoromethyl acrylic acid (TFMAA) with ethylene produced the corresponding copolymers with 6.5% ECA and 3% TFMAA incorporation. Increasing the concentration of difunctional olefins led to higher incorporation but at the expense of lower activities. These observations indicate that complex 3 tolerates difunctional vinyl monomers and provides direct access to difunctional polyolefins that have not been attempted before.

Insights into the molecular dynamics in polysulfone polymers from C-13 solid-state NMR experiments - Eldho, Kavalakal Mathai; Rajamohanan, P. R.; Anto, Ralf; Bulakh, Neelima N.; Lele, Ashish K.; Ajithkumar, Thalasseril G. (Journal of Physical Chemistry B, 2015)
The molecular and segmental motions in three different grades of ductile polysulfone polymers; poly(ether sulfone) (PESU), polysulfone (PSU), and poly(phenyl sulfone) (PPSU) are probed using C-13 solid-state NMR experiments. Polarization inversion spin exchange at magic angle (PISEMA) experiments indicates that the phenyl rings in the polymers are undergoing pi-flip motions on the order of 100 kHz. The temperature dependent PISEMA experiments show that the fraction of mobile regions that undergoes aromatic pi-flips is higher in PPSU than in the other two polymers. The center band only detection of exchange (CODEX) experiments was carried out and was unable to detect any slow segmental motions in the chains. A combination of C-13 spin-lattice relaxation time (T-1) and T-1-filtered PISEMA experiments show that the mobile regions in all the polymers are dynamically heterogeneous.

Pyrazine-based organometallic complex: synthesis, characterization, and supramolecular chemistry - Bhowmick, Sourav; Chakraborty, Sourav; Das, Atanu; Rajamohanan, P. R.; Das, Neeladri (Inorganic Chemistry, 2015)
The design, synthesis, and characterization of a new pyrazine-based ditopic platinum(II) organometallic complex are reported. The molecular structure of the organoplatinum pyrazine dipod was determined by single-crystal X-ray crystallography. The potential utility of this organometallic ditopic acceptor as a building block in the construction of neutral metallasupramolecular macrocycles containing the pyrazine motif was explored. Pyrazine motifs containing supramolecules were characterized by multinuclear NMR (including H-1 DOSY), mass spectrometry, and elemental analysis. The geometry of each supramolecular framework was optimized by employing the PM6 semi-empirical molecular orbital method to predict its shape and size. The ability of the pyrazine-based organoplatinum complex to act as a host for nitroaromatic guest (2,4-dinitrotoluene and PA) molecules was explored by isothermal titration calorimetry (ITC). The binding stoichiometry and thermodynamic parameters of these host guest complexation reactions were evaluated using ITC. Theoretical calculations were performed to obtain insight into the binding pattern between the organometallic host and nitroaromatic guests. The preferable binding propensity of the binding sites of complex 1 for both nitroaromatics (PA and 2,4-dinitrotoluene) determined by molecular simulation studies corroborates well with the experimental results as obtained by ITC experiments.

Reversed reactivity of anilines with alkynes in the rhodium-catalysed C-H activation/carbonylation tandem - Midya, Siba Prasad; Sahoo, Manoj Kumar; Landge, Vinod Gokulkrishna; Rajamohanan, P. R.; Balaraman, Ekambaram (Nature Communications, 2015)
Development of multicatalytic approach consisting of two or more mechanistically distinct catalytic steps using a single-site catalyst for rapid and straightforward access of structurally complex molecules under eco-benign conditions has significance in contemporary science. We have developed herein a rhodium-catalysed C-H activation strategy which uses an unprotected anilines and an electron-deficient alkynes to C-C bonded products as a potential intermediate in contrast to the archetypical C-N bonded products with high levels of regioselectivity. This is followed by carbonylation of C-H bond activated intermediate and subsequent annulation into quinolines has been described. This rhodium-catalysed auto-tandem reaction operates under mild, environmentally benign conditions using water as the solvent and CO surrogates as the carbonyl source with the concomitant generation of hydrogen gas. The strategy may facilitate the development of new synthetic protocols for the efficient and sustainable production of chemicals in an atom-economic way from simple, abundant starting materials.

Star telechelic poly(L-lactide) ionomers - Kulkarni, Amruta; Lele, Ashish K.; Sivaram, Swaminathan; Rajamohanan, P. R.; Velankar, Sachin; Chatterji, Apratim (Macromolecules, 2015)
Poly(L-lactide) (PLA), a biodegradable and biorenewable polymer, has many excellent properties that are equivalent to those of petroleum-derived plastics such as polystyrene, aromatic polyesters, etc. However, a major disadvantage of PLA which limits its processability is its poor melt elasticity. In this work we explore the possibility of improving the viscoelastic properties of PLA melt by incorporating ionic groups on the polymer. Specifically, we demonstrate the synthesis of star telechelic PLA anionomers by a three-step procedure involving synthesis of Star PIA, converting the hydroxyl end groups into carboxylic acid end groups, and finally converting these into ionic groups. Rheology data showed a dramatic increase in the elasticity of the star telechelic ionomer melts relative to the Star PLA melts. The viscoelasticity of star telechelic ionomers melts could be modulated by varying the number of ionic groups per molecule.

Synthesis and characterization of PEPO grafted carboxymethyl guar and carboxymethyl tamarind as new thermo-associating polymers - Gupta, Nivika R.; Torris, Arun A. T.; Wadgaonkar, Prakash P.; Rajamohanan, P. R.; Ducouret, Guylaine; Hourdet, Dominique; Creton, Costantino; Badiger, Manohar V. (Carbohydrate Polymers, 2015)
New thermo associating polymers were designed and synthesized by grafting amino terminated poly(ethylene oxide-co-propylene oxide) (PEPO) onto carboxymethyl guar (CMG) and carboxymethyl tamarind (CMT). The grafting was performed by coupling reaction between-NH2 groups of PEPO and -COOH groups of CMG and CMT using water-soluble EDC/NHS as coupling agents. The grafting efficiency and the temperature of thermo-association, T-assoc in the copolymer were studied by NMR spectroscopy. The graft copolymers, CMG-g-PEPO and CMT-g-PEPO exhibited interesting thermo-associating behavior which was evidenced by the detailed rheological and fluorescence measurements. The visco-elastic properties (storage modulus, G'; loss modulus, G'') of the copolymer solutions were investigated using oscillatory shear experiments. The influence of salt and surfactant on the T-assoc was also studied by rheology, where the phenomenon of ``Salting out'' and ``Salting in'' was observed for salt and surfactant, respectively, which can give an easy access to tunable properties of these copolymers. These thermo-associating polymers with biodegradable nature of CMG and CMT can have potential applications as smart injectables in controlled release technology and as thickeners in cosmetics and pharmaceutical formulations. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carboxymethyl guar; Carboxymethyl tamarind; Pluronics; Rheology; Solution behavior; Thermo-associating polymers

Total synthesis and structural revision of mycalol, an anticancer natural product from the marine source - Seetharamsingh, B.; Rajamohanan, P. R.; Reddy, D. Srinivasa (Organic Letters, 2015)
The total synthesis of an anticancer (anaplastic thyroid) natural lipid mycalol has been accomplished for the first time. Synthesis of originally proposed structure necessitated the revision of structure in which the position of acetate group moved from C20 to C19 and a change in stereochemistry of the glycerol unit.

Disruption of native beta-turns: consequence of folding competition between native and orthanilic acid proline-based pseudo beta-turn - Ingole, Tukaram S.; Vijayadas, Kuruppanthara N.; Chaitanya, K. N.; Kotmale, Amol S.; Gawade, Rupesh L.; Gonnade, Rajesh G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (European Journal of Organic Chemistry, 2016)
Five tetrapeptides comprising beta-turn-forming elements and a pseudo beta-turn (C9 H-bonding) based on an SAntPro (orthanilic acid - proline) motif were designed and synthesized. Their extensive conformational investigation by single-crystal X-ray crystallography, solution-state 2D NMR spectroscopic, and nOe-restrained MD simulation studies revealed the formation of C14 or C9 folding and disruption of the native beta-turn (C10 H-bonding) architecture. The striking difference between the psi(psi(2)) angle of ``i + 2'' residues of native beta-turn and designed peptides suggest that formation of the native beta-turn is not favored. The results suggest that other turn-forming motifs can dramatically modulate the stability of the native beta-turn structure.
Keywords: Conformation analysis; hydrogen bonds; Peptidomimetics; structure elucidation

Acyclic αγα-tripeptides with fluorinated- and nonfluorinated-furanoid sugar framework: importance of fluoro substituent in reverse-turn induced self-assembly and transmembrane ion-transport activity - Burade, S. S.; Shinde, S. V.; Bhuma, N.; Kumbhar, N.; Kotmale, A.; Rajamohanan, P. R.; Gonnade, R. G.; Talukdar, P.; Dhavale, D. D. (Journal Of Organic Chemistry, 2017)
Acyclic αγα-tripeptides derived from fluorinated-furanoid sugar amino acid frameworks act as reverse-turn inducers with a U-shaped conformation, whereas the corresponding nonfluorinated αγα-tripeptides show random peptide conformations. The NMR studies showed the presence of bifurcated weak intramolecular hydrogen bonding (F···HN) and N+···Fδ- charge-dipole attraction compel the amide carbonyl groups to orient antiperiplanar to the C-F bond, thus, demonstrating the role of the fluorine substituent in stabilizing the U-shaped conformation. The NOESY data indicate that the U-shaped tripeptides self-assembly formation is stabilized by the intermolecular hydrogen bonding between C=O···HN with antiparallel orientation. This fact is supported by ESI-MS data, which showed mass peaks up to the pentameric self-assembly, even in the gas phase. The morphological analysis by FE-SEM, on solid samples, showed arrangement of fibers into nanorods. The antiparallel self-assembled pore of the fluorinated tripeptides illustrates the selective ion-transport activity. The experimental findings were supported by DFT studies.

Chiral discrimination through h-1 nmr and luminescence spectroscopy: dynamic processes and solid strip for chiral recognition - Gangopadhyay, Monalisa; Maity, Arunava; Dey, Ananta; Rajamohanan, P. R.; Ravindranathan, Sapna; Das, Amitava (Chemistry-A European Journal, 2017)
The appropriate choice of the host molecules with well-defined optical activity (S-H/R-H) helps in the differentiation between two secondary ammonium ion-derivative guest molecules with different optical activities (R-G/S-G) based on the fluorescence resonance energy transfer (FRET)based luminescence responses. Crown ether-based host molecules with opposite chiral configurations (R-H, S-H) have been derived from 1,1'-bi-2-naphthol (BINOL) derivatives that have axially chiral biaryl centers. These chiral crown ethers form host-guest complexes (i.e., [2] pseudoro-taxanes) with chiral secondary ammonium ion derivatives (R-G, S-G). NMR spectroscopic studies show that the complexes are in a dynamic equilibrium in solution. Results of the H-1 NMR and fluorescence spectroscopic studies indicate a head-on orientation of the host and guest in the [2] pseudorotaxanes. The difference in the efficiency in the FRET-based responses between anthracene and the BINOL derivatives allow efficient chiral discrimination of the guests. Isothermal titration calorimetry and NMR investigations reveal that inclusion complexes between hosts and guests of the same chirality (R-H center dot R-G, S-H center dot S-G) are more stable relative to those of opposite chirality (R-H center dot S-G, S-H center dot R-G). However, FRET-based energy-transfer efficiency is higher for R-H center dot S-G and S-H center dot R-G complexes. NMR spectroscopic studies show that the relative orientation of the guest in the host cavity is significantly different when the host binds a guest of the same or opposite chirality; furthermore, the latter is more favorable for FRET, thus enabling discrimination between enantiomers. Interestingly, chiral discrimination of guest ions could also be achieved by using silica surfaces modified with chiral host molecules.

Molecular motifs for additives that retard PEO crystallization - Shrivastava, Sudhakar Dinesh; Eldho, Kavalakal Mathai; Rajamohanan, P. R.; Ajithkumar, Thalasseril G.; Vanka, Kumar; Kumaraswamy, Guruswamy (Polymer Engineering & Science, 2017)
We investigate the influence of several bifunctional phenol additives (resorcinol: RES, hydroquinone: HYD, p-hydroxybenzoic acid: PHBA, and p-nitrophenol: PNP) on the crystallization of matrix polymer, polyethyleneoxide. We employ solid state Nuclear Magnetic Resonance spectroscopy (NMR), Differential Scanning Calorimetry (DSC), optical microscopy, and Small Angle X-ray Scattering (SAXS) to investigate crystallization of the additivated PEO and compare with Density Functional Theory (DFT) calculations of additive-PEO interactions. Additive-polymer interactions are a function of the functional groups on the additive. Temperature-dependent spherulitic growth rate measurements from optical microscopy and SAXS lamellar long spacings indicate a distinct trend in the effect of additives on PEO crystallization. Change in PEO crystallization is most pronounced with PNP, followed by PHBA and finally RES and HYD. This trend correlates qualitatively with the binding energies of additive-PEO interactions from DFT studies. Our results suggest that DFT calculations might be a useful screening tool to evaluate the influence of additives on polymer crystallization. POLYM. ENG. SCI., 2016. © 2016 Society of Plastics Engineers

Mechanism of the formation of microphase separated water clusters in a water-mediated physical network of perfluoropolyether tetraol - Deshpande, Ashwini A.; Torris, Arun A. T.; Pahari, Swagata; Menon, Shamal K.; Badiger, Manohar V.; Rajamohanan, P. R.; Wadgaonkar, Prakash P.; Roy, Sudip; Tonelli, Claudio (Soft Matter, 2018)
Perfluoropolyether tetraol (PFPE tetraol) possesses a hydrophobic perfluoropolyether chain in the backbone and two hydroxyl groups at each chain terminal, which facilitates the formation of hydrogen bonds with water molecules resulting in the formation an extended physical network. About 3 wt% water was required for the formation of the microphase separated physical network of PFPE tetraol. The mechanism responsible for the microphase separation of water clusters in the physical network was studied using a combination of techniques such as NMR spectroscopy, molecular dynamics (MD) simulations and DSC. MD simulation studies provided evidence for the formation of clusters in the PFPE tetraol physical network and the size of these clusters increased gradually with an increase in the extent of hydration. Both MD simulations and NMR spectroscopy studies revealed that these clusters position themselves away from the hydrophobic backbone or vice versa. The presence of intra-and inter-chain aggregation possibility among hydrophilic groups was evident. DSC results demonstrated the presence of tightly and loosely bound water molecules to the terminal hydroxyl groups of PFPE tetraol through hydrogen bonding. The data from all the three techniques established the formation of a physical network driven by hydrogen bonding between the hydrophilic end groups of PFPE tetraol and water molecules. The flexible nature of the PFPE tetraol backbone and its low solubility parameter favour clustering of water molecules at the terminal groups and result in the formation of a gel.

Thermo thickening behavior of MPEG-b-PCL grafted poly(acrylic acid): a molecular insight - Tiwari, Neha (Polymer, 2018)
We report on the synthesis and characterization of a new thermothickening polymer (PAA-g-(MPEG-b-PCL)) based on the grafting of a block copolymer of mono methoxy poly (ethylene glycol)–b-poly (caprolactone) (MPEG-b-PCL) onto poly (acrylic acid) (PAA). Rheological experiments reveal that aqueous solutions of PAA-g-(MPEG-b-PCL) exhibit interesting irreversible thermothickening behavior above a certain polymer concentration and critical temperature. Light scattering experiments show that increasing temperature induces hydrophobic associations and subsequent aggregation leading to gel formation which is irreversible. The mechanism of thermo thickening was examined at the molecular level by NMR methods which indicated unassembled and assembled environments of the MPEG-b-PCL grafts. On heating, interactions between the graft side chains are significantly enhanced and molecular mobility in the assembled microdomains is reduced. The stable well ordered microdomains that are formed on heating are retained on cooling thus, leading to irreversible gelation.
Keywords: Hydrophobically modified poly (acrylic acid); Light scattering; Methoxy polyethylene glycol-b-polycaprolactone (MPEG-b-PCL) copolymer; Rheology; Thermo gelation

Aromatic polycarbonates bearing pendant maleimide groups via functional monomer approach: synthesis and characterization - Nagane, Samadhan S.; Kuhire, Sachin S.; Ichake, Amol B.; Rajamohanan, P. R.; Wadgaonkar, Prakash P. (Journal of Polymer Research, 2019)
A new bisphenol containing pendant maleimide group, viz., 4, 4'-(5-maleimidopentane-2, 2-diyl) diphenol (BPA-MA), was synthesized starting from commercially available 4, 4'-bis (4-hydroxyphenyl) pentanoic acid. Aromatic (co)polycarbonates possessing pendant maleimide groups were synthesized by solution polycondensation of BPA-MA or varying mixtures of BPA-MA and bisphenol-A (BPA) with triphosgene in dry dichloromethane in the presence of triethylamine as a base. Inherent viscosities and number average molecular weights of (co)polycarbonates were in the range 0.46-0.66 dL/g and 24,600-36,700, respectively, indicating the formation of reasonably high molecular weight polymers. Tough, transparent, and flexible films could be cast from chloroform solutions of these (co)polycarbonates. (Co)polycarbonates were characterized using FT-IR, H-1 NMR, C-13 NMR spectroscopy, XRD, TGA and DSC analysis. The chemical modification of a representative copolycarbonate containing pendant maleimide groups was carried out quantitatively using thiol-maleimide Michael addition reaction with two thiol compounds, namely, 4-chlorothiophenol and 1-adamantanethiol. Additionally, it was demonstrated that copolycarbonate containing pendant maleimide groups could be used to form insoluble cross-linked gel by reaction with a multifunctional thiol cross-linker, namely, pentaerythritol tetrakis(3-mercaptopropionate).
Keywords: Aromatic polycarbonate; Cross-linking; maleimide group; Thiol-maleimide reaction; Triphosgene

Development of a nano-gold immunodiagnostic assay for rapid on-site detection of invasive aspergillosis - Raval, Komal M.; Ghormade, Vandana; Rajamohanan, P. R.; Choudhary, Hansraj; Rudramurthy, Shivaprakash M.; Chakrabarti, Arunaloke; Paknikar, Kishore (Journal of Medical Microbiology, 2019)
Introduction. Timely detection of invasive aspergillosis (IA) caused by fungal pathogens, i.e. Aspergillus fumigatus and Aspergillus flavus, in immunocompromised patients is crucial in preventing high mortality. Aim. To develop a simple immunoassay for the detection of galactomannan (GM), an IA biomarker. Methodology. GM from A. fumigatus and A. flavus clinical strains was purified and characterized by X-ray diffraction, IR spectroscopy and C-13/H-1 nuclear magnetic resonance (NMR) for polyclonal antibody (pAb) production in rabbits. An enzyme-linked immunosorbent assay (ELISA) was standardized using concanavalin A to capture Aspergillus GM and pAbs to detect it. Gold nanoparticles (AuNPs) were synthesized and conjugated to pAbs for the development of a dot-blot immunoassay. The developed dot-blot was evaluated with 109 clinical serum and bronchoalveolar lavage samples. Results. Spectroscopy studies characterized the D-galactofuranosyl groups of GM responsible for the immune response and generation of pAbs. The ELISA employing pAbs showed a sensitivity of 1 ng ml(-1) for Aspergillus GM. Furthermore, a sensitive, visual, rapid dot-blot assay developed by the conjugation of pAbs to AuNPs (similar to 24 +/- 5 nm size, -36 +/- 2 mV zeta potential) had a detection limit of 1 pg ml(-1) in serum. The pAbs interacted with Aspergillus spp. but did not cross-react with other fungal pathogen genera such as Penicillium and Candida. Evaluation of the dot-blot with 109 clinical samples showed high sensitivity (80%) and specificity (93.2 %), with an overall assay accuracy of 89%. Conclusion. The developed nano-gold immunodiagnostic assay has immense potential for practical use in rapid, specific and sensitive on-site diagnosis of IA, even under resource-limited settings.

Insight Into the Influence of Salinity on Flow and Flocculation Behavior of Acrylamide-Based Cationic Polyelectrolyte - Ranganath, Suresha P.; Kurian, Rachna; Torris, Arun; Khairnar, Ajay; Ravindranathan, Sapna; Rajamohanan, P. R.; Badiger, Manohar V.; Wolf, Bernhard A. (Journal of Applied Polymer Science, 2026)
The viscometric behavior of aqueous solutions of acrylamide and acrylamidopropyl trimethylammonium chloride copolymers (AM-co-APTMAC) with varying cationic content under different salinity conditions was studied. Viscometric measurements were employed to determine intrinsic viscosity and quantify the influence of electrostatic interactions on chain conformation. Rheology experiments were performed to probe dynamic flow behavior under shear to obtain insights into polyelectrolyte viscoelastic properties under conditions mimicking industrial processes. Viscometric and rheology data analysis is augmented with insights from NMR relaxation and pulsed field gradient NMR diffusion experiments. Further, flocculation of kaolin suspensions was studied using aqueous solutions of AM-co-APTMAC copolymers with different charge fractions in the presence and absence of salt. The physicochemical insights on the behavior of AM-co-APTMAC polyelectrolytes in solution from this study could be relevant in practical applications, such as plants that use seawater or in cases where the ionic strength of suspensions is high due to salinity in the medium.
Keywords: copolymers; polyelectrolytes; structure property relationships; theory and modeling